Health care reform and universal coverage - Guzmán Changanaqui, Alfredo (2015)
Peruvian health system, with nearly 70 years of institutionality, unable so far to solve the pressing health problems of the country and excludes a quarter of the population of the possibility of access to health services. Furthermore, it allows a fragmentation of the health system in four subsectors: the Ministry of Health, the Ministry of Labour with EsSalud, the Ministry of Defence with the healing of the army, navy and air force and the Ministry of Interior police health . This fragmentation causes duplication of investments, policy conflicts, parallel rectories and inefficient spending in a country where public spending on health is well below the average for the region. What is needed is a major health reform to end the existing institutional fragmentation and, through a universal insurance, allow access of all people to a health system oriented especially disease prevention and recovery health, articulating collective and individual protection and complementary effort of public and private stakeholders to achieve comprehensive health care with social justice ,. equity, quality and efficiency.